Ecological production as a market regulator for the pork market in the county of Osijek and Baranja - Tolušić, Zdravko (Acta agriculturae Slovenica, 2004)
The objective of this research was to examine our consumers' perception of thehigh-quality ecologically produced meat and to ascertain to what extent this form of production and the quality of thus obtained pork can influence the pork market flows and be a regulator of this market. Based on the results of our research, we may conclude that pork is an important foodstuff in the diet of the residents of the County of Osijek and Baranja, since more than 80% of our subjects eat pork at least once a week. Price, instead of quality, is still the most important criterion for the purchasing of meat. More than 40% of the subjects pay no attention to the origin of meat when purchasing it, and a third of them do not check whether the meat is suitable in terms of health. Although the entire population is aware of the ecological method of pig-breeding, almost a third of them do not consider this method of pork production positive. Half of the subjects are not ready to pay a higher price for the meat produced by means of the ecologically acceptable method, in spite of the fact that they believe such meat to be of higher quality. Due to this reason, at this moment ecologically produced pork does not have a notable effect on market flows and market regulation. In order to obtain such an effect, certain requirements need to be fulfilled. This pertains primarily to the growth of the purchasing power of the population, ecological awareness and changes in the diet of our population towards the consumption of healthier foods.
Keywords: ekološka reja; Hrvaška; prašiči; svinjsko meso; trženje